New compression mechanism in penile-scrotal lymphedema and sexual rehabilitation - Jose Maria Pereira de Godoy; Fernando Nestor Facio; Eleni Cássia Matias de Carvalho; Maria de Fatima Guerreiro Godoy (Urology Annals, 2014)
The objective of this study is to describe a new compression mechanism in the treatment of lymphedema of the penis and scrotum and the ensuing sexual rehabilitation. The patient, a 58-year-old man, had edema of the penile and scrotal region as a result of surgery of the pancreas and spleen and chemotherapy. The patient complained of pain, discomfort, and difficulties to walk and urinate. A clinical diagnosis of lymphedema of the penis and scrotum was reached. Treatment involved the continuous use of a cotton-polyester compression garment for the region together with thorough hygiene skin care. The swelling reduced significantly within a week to almost a normal aspect which was accompanied by clinical improvements of the symptoms. The reduction in penile edema allowed sexual rehabilitation even though erectile dysfunction required the use of a specific medication (sildenafil). In conclusion, simple and low-cost options can improve lymphedema of the penis and scrotum and allow sexual rehabilitation.